2023
DOI: 10.3390/v15040914
|View full text |Cite
|
Sign up to set email alerts
|

Both Feline Coronavirus Serotypes 1 and 2 Infected Domestic Cats Develop Cross-Reactive Antibodies to SARS-CoV-2 Receptor Binding Domain: Its Implication to Pan-CoV Vaccine Development

Abstract: The current study was initiated when our specific-pathogen-free laboratory toms developed unexpectedly high levels of cross-reactive antibodies to human SARS-CoV-2 (SCoV2) receptor binding domain (RBD) upon mating with feline coronavirus (FCoV)-positive queens. Multi-sequence alignment analyses of SCoV2 Wuhan RBD and four strains each from FCoV serotypes 1 and 2 (FCoV1 and FCoV2) demonstrated an amino acid sequence identity of 11.5% and a similarity of 31.8% with FCoV1 RBD (12.2% identity and 36.5% similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Higher seroprevalence in cats compared to dogs has been described [ 62 ]. However, it has been reported that some cats infected with feline coronavirus can develop cross-reactive antibodies to SARS-CoV-2 that could be contributing to the SARS-CoV-2 seroprevalence seen in cats [ 63 , 64 ]. Without underlying health conditons or co-infections, productive SARS-CoV-2 infection may be subclinical in many species; therefore, animal cases may be under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…Higher seroprevalence in cats compared to dogs has been described [ 62 ]. However, it has been reported that some cats infected with feline coronavirus can develop cross-reactive antibodies to SARS-CoV-2 that could be contributing to the SARS-CoV-2 seroprevalence seen in cats [ 63 , 64 ]. Without underlying health conditons or co-infections, productive SARS-CoV-2 infection may be subclinical in many species; therefore, animal cases may be under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…The FCoV Membrane (M) protein is a glycosylated structural protein anchored in the viral envelope [ 41 ]. FCoV M is the most abundant viral structural protein and has a size variably defined as 25–30 kDa [ 39 ] or 28–32 kDa [ 42 ]. Although abundantly distributed throughout the viral envelope, M protein has a relatively small ectodomain, which makes it less antigenic [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FCoV Nucleocapsid (N) protein binds the viral genomic RNA and protects it from degradation [ 39 ]. The size of FCoV N has been described as ranging from 43 kDa [ 42 ] to 50 kDa [ 39 ]. The FCoV spike (S) protein forms a trimer on the viral envelope and is the primary ligand facilitating cell entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent COVID-19 pandemic caused by the highly pathogenic coronavirus SARS-CoV-2 with animal origin has further highlighted the relevance of animal companion virology to global health [18]. Last but not the least, feline virus infection is an important animal model for human viral diseases such as calicivirus or coronavirus infection [19,20]. Considering few reports on the epidemiological survey of feline infectious diseases in China, this study aimed to investigate the prevalence of FPV, FCV, FHV-1, and FCoV in cats in China.…”
Section: Introductionmentioning
confidence: 99%